Properties of Helical Structures with Internal Anisotropic Shields - Daskevicius, V.; Skudutis, J.; Staras, S. (Elektronika ir Elektrotechnika, 2013)
Properties of the helical structures with internal anisotropic shields are considered in the paper. Models of systems based on the multiconductor line method and the CST Microwave Studio software package are used. The expressions for the retardation factor and the input impedance of the system are derived using the multiconductor line method. Analysis of the retardation factor allowed to show that there are possibilities to design helical structures with internal anisotropic shields having good dispersion properties and relatively high characteristic impedance. Simulation made using the CST Microwave Studio package confirmed the properties of the systems revealed using the multiconductor line method. Furthermore, in addition it allowed the detection of parasitic resonances that are available in helical systems with anisotropic internal shields. Synergy of various methods can be effectively used at analysis and design of wide-band periodic structures. DOI: http://dx.doi.org/10.5755/j01.eee.19.1.3256